MENINGKATKAN KEMAMPUAN BERBICARA MELALUI METODE BERCERITA DENGAN MEDIA BONEKA TANGAN PADA ANAK USIA 4-5 TAHUN - Yuni Yuliawati, Eneng Sri Susilawati, Subhan (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
This study aims (1). To improve children's speaking ability through storytelling method using hand puppet media (2). To analyze the improvement of children's speaking ability through storytelling method using hand puppet media. First supervisor: Dr. Eneng Sri Susilawati M.Pd. Supervisor II: H.Subhan, M.Pd. Setia Budhi University (USB) Rangkasbitung 2024. This research was conducted at PAUD Al Fajar, Tanara District, Serang Regency. This study uses a type of Classroom Action Research (PTK) research. The data collection techniques used were observation, documentation, and children's worksheets. The research subjects were children aged 4-5 years at PAUD Al Fajar, Tanara District, Serang Regency. The results showed that learning through pop up media can improve the speaking ability of children aged 4-5 years at PAUD Al Fajar, Tanara District, Serang Regency. The success rate in children increased. In pre-cycle activities from an average of 38.61% increased 23.63% in cycle I to 62.24% then increased again 17.44% in cycle II to 79.68%.